METHODS OF ASSESSING THE ECONOMIC EFFICIENCY OF THE INDUSTRIAL SECTOR AND THEIR IMPROVEMENT - Kasimov Azamat Abdukarimovich (American Journals, 2025)
This article examines in detail the economic efficiency indicators of the industrial sector and their calculation methods. Using existing methods, their improved methods and boundary criteria are proposed. Also, based on these methods, the economic efficiency of the industrial sector's resources is assessed and analyzed. In addition, proposals are developed to improve the economic efficiency of the industrial sector.
Keywords: Industry, efficiency, economic efficiency of the industrial sector, evaluation methods, evaluation criteria.